2013
DOI: 10.1007/s12350-013-9714-2
|View full text |Cite
|
Sign up to set email alerts
|

Significance of I-123 metaiodobenzylguanidine (123I-MIBG) lung activity in subjects with heart failure in comparison to healthy control subjects

Abstract: Increased (123)I-MIBG lung activity in heart failure subjects, compared to controls, is associated with a relatively low risk of adverse events, including all-cause mortality. L/M ratio may, therefore, be useful to provide incremental prognostic information on (123)I-MIBG imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…Increased MIBG uptake is known to be associated with improved prognosis in heart failure patients (Gerson et al 2013). However, in the present study, there were no cardiopulmonary symptoms in the patients with increased lung uptake, and the reason for lung uptake could not be identified.…”
Section: Discussioncontrasting
confidence: 78%
“…Increased MIBG uptake is known to be associated with improved prognosis in heart failure patients (Gerson et al 2013). However, in the present study, there were no cardiopulmonary symptoms in the patients with increased lung uptake, and the reason for lung uptake could not be identified.…”
Section: Discussioncontrasting
confidence: 78%
“…Lung-to-mediastinal ratios in combination with H/M values are associated with all cause mortality and rate of events in patients with heart failure. 16,17 Previous studies from the authors' group have also shown the feasibility of performing simultaneous LV perfusion and innervation with a CZT camera. 18 However, this is the first study to apply this concept to the right ventricle.…”
mentioning
confidence: 98%
“…4,20 Lung uptake of mIBG has also been evaluated for its prognostic value in patients with heart failure with reduced ejection fraction. 21,22 Kamiyoshi et al reported that the lung/heart ratio was found to be an independent predictor of cardiac events. 22 Gerson and colleagues also published evidence of the prognostic utility of the lung/mediastinum ratio.…”
mentioning
confidence: 99%
“…22 Gerson and colleagues also published evidence of the prognostic utility of the lung/mediastinum ratio. 21 It is ironic that the highly sophisticated imaging and reconstruction techniques introduced over the past decade or two have provided no further advantage when imaging with mIBG when compared to the comparatively primitive H/M ratio. This ratio is, in its essence, a simple measure of global adrenergic activity of the heart.…”
mentioning
confidence: 99%